The role of coronary artery calcium estimation in the primary prevention strategy for cardiovascular diseases - Kolesnyk, M. Yu. (Zaporozhye Medical Journal, 2023)
Calcification is one of the stages of complicated and uncomplicated atherosclerotic plaque development. Determination of calcium deposits in the composition of plaques by the method of multispiral computer tomography allows to assess the coronary atherosclerotic lesion severity. The advantages of the test include a relatively wide availability, low cost and dose of ionizing radiation, as well as no need to inject a contrast agent. Calculation of the coronary artery calcium (CAC) according to the Agatston method is the “gold standard” for quantitative assessment of the coronary atherosclerosis severity. The review highlights modern ideas about the role of the test in primary prevention in people without diagnosed cardiovascular disease. Methodological principles of determining coronary calcium are explained. The principles of test result interpretation and presentation based on the international СAC-RADS scale are described. Data from population studies on the prevalence of coronary calcification in people without cardiovascular disease in different age categories are provided. The results of the prognostic value of CAC based on the analysis of large population studies are presented. The prognostic value of a negative test (CAC = 0) for coronary calcium is discussed. Data are presented on the recommended frequency of repeated examinations in patients with CAC = 0 depending on an individual cardiovascular risk. The data of randomized clinical trials on the expediency of determining coronary calcium in certain age categories are given. The place of the test in international clinical recommendations for the primary prevention of cardiovascular diseases is analyzed. Research findings on a personalized approach to prescribing statins and aspirin based on coronary calcium test results are discussed. Data are provided on improved adherence in patients with coronary calcium screening compared with the standard approach. The limitations and shortcomings of the test are analyzed separately, among which the impossibility of controlling the effectiveness of hypolipidemic therapy with statins in dynamics can be identified. An integrated approach to the role of the coronary calcium test based on the analysis of current international clinical recommendations is provided.